Planning Practices for the Protection of Cultural Heritage: Lessons Learnt from the Greek UNESCO Sites - Papageorgiou, Marilena (European Spatial Research and Policy, 2015)
As in all countries worldwide, in Greece too, sites selected to become part of the UNESCO’s world heritage are representative samples of the country’s monumental heritage and therefore constitute exemplars of planning adopted for their spatial protection.By the case study conducted in the Greek UNESCO sites, it was revealed that, despite the fact that most of the monuments are subjects of multiple zoning, little is accomplished for their spatial protection. This is either because zoning and planning launched by the Ministry for the Environment is absent or taking too long to get approved or because zoning deriving from the Ministry of Culture is void of spatial regulations. This means that on the one hand the Ministry for the Environment should proceed at a faster pace to the elaboration of Local Spatial Plans that are necessary especially in the case of monuments in rural settings, while on the other hand the Ministry of Culture should immediately proceed to the revision of Protection Zones A and B, so they fall into the guidelines of the new Law 3028 and they acquire spatial restrictions and regulations; a condition that can only be achieved with the collaboration among Spatial Planners and Archaeologists and among competent bodies.